Accounting students' perception on the use of programming software for analysis and design of accounting information systems: some empirical findings - Zainol, Zaini; Puat Nelson, Sherliza (Unpublished, 2011)
Programming based subjects are perceived by many students as one of the most difficult subjects. Other than non computer science students who felt the pinch on this difficult subject, those from computer and engineering programme have similar experience too. In the social sciences such as, in the accounting programme, designing an accounting database system has also become among the required courses. Academically, the accounting students are trained to do accounting. Hence, designing a database is something not within their radar. The study tried to seek some explanation on why this perception surfaced.Therefore, the aim of this research is to investigate accounting students’ self-efficacy factors and its relationship with attitude and satisfaction of using Microsoft Access TM database programming software. The study used Microsoft AccessTM as database software for accounting database assignment because this software is more user-friendly, as compared to the more technical programming software such as C++, Java, Fotran and MySQL. As far as accounting students are concerned, we do not expect them to have an in depth knowledge in programming especially in database programming. The sample consists of accounting students enrolled in analysis and design of accounting information systems (ADAIS) course, during the semester. The students are required to develop an accounting database for one of four organisations namely budget hotel, clinic, private school, and restaurant, for their assignments.Consequently, the students were given this questionnaire on self efficacy to be answered. Six factors are examined namely gender, internet skills, skills of using Microsoft office application, prior working experience, ownership of computer and perceived future role as an accountant in accounting information system environment. Findings revealed mixed results and are discussed further in the paper. The findings contributed to the existing self efficacy literature and are useful for future enhancement of accounting information system syllabus.